2010
DOI: 10.1111/j.1365-2710.2009.01107.x
|View full text |Cite
|
Sign up to set email alerts
|

REVIEW ARTICLE: Toenail onychomycosis: an important global disease burden

Abstract: Summary Onychomycosis is a fungal infection of the nail plate or nail bed. It does not usually cure itself and it can trigger more infectious lesions in other parts of the body. The reported prevalence of onychomycosis is increasing in Western countries, presumably due to lifestyle changes and the ageing of the population. Approximately 10% of the general population, 20% of the population aged >60 years, up to 50% of people aged >70 years and up to one‐third of diabetic individuals have onychomycosis. Care sho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
275
0
14

Year Published

2012
2012
2018
2018

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 287 publications
(295 citation statements)
references
References 156 publications
6
275
0
14
Order By: Relevance
“…14 Some authors have postulated that this gender difference may be due to differences in hormone levels that result in a different capacity to inhibit the growth of dermatophytes. [14][15][16][17] We observed that fingernails (69.84%) were most commonly affected site followed by toenails (19.84%). In 65 (10.32%) patients both the finger and toenails were affected.…”
Section: Discussionmentioning
confidence: 99%
“…14 Some authors have postulated that this gender difference may be due to differences in hormone levels that result in a different capacity to inhibit the growth of dermatophytes. [14][15][16][17] We observed that fingernails (69.84%) were most commonly affected site followed by toenails (19.84%). In 65 (10.32%) patients both the finger and toenails were affected.…”
Section: Discussionmentioning
confidence: 99%
“…1,2 Dermatomycosis usually manifests as itchy, sore skin rashes and tinea on the toes, the inner thighs or groin; leading to flaking and blistering of the affected area. Fungi may spread to the scalp or nails causing hair loss and thickened or deformed fingernails.…”
Section: Introductionmentioning
confidence: 99%
“…Trichophyton rubrum is the main culprit of superficial mycosis of the nail (onychomycosis), which is often long lasting and has a high incidence of recurrence. Onychomycosis affects 10% of the general population, 20% of the population older than 60 years, 50% of people older than 70 years, and 30% of diabetic patients, and it can often result in pain, disability, and psychosocial stress, therefore significantly reducing quality of life (1)(2)(3). The conventional treatments involve excruciating surgical nail avulsion and toxic systemic antifungal drugs.…”
mentioning
confidence: 99%